2023
DOI: 10.3390/foods12244490
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Prospects of Plant-Protein-Based 3D Printing

Shivani Mittal,
Md. Hafizur Rahman Bhuiyan,
Michael O. Ngadi

Abstract: Three-dimensional (3D) printing is a rapidly developing additive manufacturing technique consisting of the deposition of materials layer-by-layer to produce physical 3D structures. The technique offers unique opportunities to design and produce new products that cater to consumer experience and nutritional requirements. In the past two decades, a wide range of materials, especially plant-protein-based materials, have been documented for the development of personalized food owing to their nutritional and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…10–12 Despite these advantages, plant proteins, especially those from legumes and cereals, present challenges, such as limited solvent compatibility, which hinders their application as biomaterials. 13 Since the biocompatibility of plant proteins remains unclear, further evaluation of their potential immunogenicity and derivatives is required. Considering the abundant availability and the low immunogenicity and cost of plant proteins, it is profitable to develop bioinks derived from plant proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10–12 Despite these advantages, plant proteins, especially those from legumes and cereals, present challenges, such as limited solvent compatibility, which hinders their application as biomaterials. 13 Since the biocompatibility of plant proteins remains unclear, further evaluation of their potential immunogenicity and derivatives is required. Considering the abundant availability and the low immunogenicity and cost of plant proteins, it is profitable to develop bioinks derived from plant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…18–21 Moreover, a few studies have reported utilizing plant proteins as raw material for bioinks used in tissue engineering, but with a focus on food printing, such as cellular meat. 13,17,18 For example, bovine muscle cells have been cultured on inexpensive and sustainable three-dimensional plant protein scaffolds; David et al investigated two processing techniques for solubilising pea proteins, which led to the fabrication of cost-effective, protein-rich scaffolds with high nutritional value, thus greatly facilitating the commercial production of cultured meat. 22,23 Hence, the primary focus lies in enhancing the water solubility of bioinks derived from plant proteins and imbuing them with photocrosslinking properties for gel formation to tailor them for DLP 3D bioprinting in tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%